Assessment of the Effect of Multidrug Resistance Clostridium difficile Clinical Strains on the Dynamics of Clostridium difficile Infection Rate at Pediatric Oncological Hospital - M. G. Shvydkaya; A. M. Zatevalov; D. T. Dzhandarova; S. D. Mitrokhin; O. E. Orlova (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. At the children's oncological hospital guidelines to treat patients with several groups of antibiotics at the same time, which ensures the formation of multi-resistant strains of Clostridium difficile, which have a selective advantage for the Clostridium difficile infection developing, and also cause epidemics and /or in associating with an increase in the severity of Clostridium difficile – infection. Aims. Multidrug resistance Clostridium difficile strains and Clostridium difficile infection rate at pediatric oncological hospital. Results. An investigation of the Clostridium difficile resistance strains carried out among children at the children's oncological hospital. 143 toxigenic strains are resistant to moxifloxacin 72.41%, clindamycin 63.72%, rifampicin 35.54%, tetracycline 26.45%, tigecycline 11.42%, vancomycin 4.4%, metronidazole 3.9%. At the same time, the increase multidrug-resistant strains proportion note at the level of 3–4% per year. However, the rate of Clostridium difficile infection among children at the oncological hospital remained at the level of 0.4% to 3.1% with a downward trend. As a result, statistical calculations showed the absence of correlation between multidrug resistance and morbidity. Conclusions. Detection of multidrug-resistant microorganisms among toxigenic Clostridium difficile strains proves the need for further study of this problem in Russia and the advisability of monitoring Clostridium difficile infection rate and multidrug resistance Clostridium difficile strains at pediatric oncological hospitals.